POLA RESISTENSI Acinetobacter baumannii YANG DIISOLASI DI Intensive Care Unit (ICU) RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE 1 JANUARI HINGGA 31 DESEMBER 2014 - Venty Rahman; Dewi Anggraini; Dina Fauzia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBacterial resistance toward antibiotics occurs when antibiotics have lost their ability to effectively control or kill the growth of the bacteria. Bacterial resistance is a worldwide problem in both developing and developed countries. The purpose of this research is to know A. baumannii pattern and their antibiotics resistance isolated in an Intensive Care Unit of Arifin Achmad General Hospital in Riau Province period 1 January until 31 December 2014. This research used descriptive and retrospective design with the total number of isolates as much as 59 isolates. This study was carried out at Microbiology of the clinical Patologi Laboratory Arifin Achmad General Hospital in Riau Province using a Vitek Compact 2. The most commonly isolated bacteria of sputum culture were A. baumannii 34,7% meanwhile in blood culture A. baumannii was found as much as 1,7%. Resistance pattern showed that A. baumannii bacteria have the resistance against meropenem and the sensitivity were amikasin and tygesiclin.Keywords : Antibiotics, bacteria resistance, Intensive Care Unit, sensitivity.